Short Practical Regimen of Acupuncture for Melasma: A Prospective Cohort Study in a Tertiary Hospital in Thailand - Supasiri, Thanan; Salakshna, Nuntida; Pongpirul, Krit (Frontiers in Public Health, 2021)
Background: Acupuncture shows benefits for patients with melasma, although no optimal number of sessions have been determined. Methods: The prospective observational study was conducted in melasma patients who were treated with acupuncture procedures two times a week and were evaluated after the 5th and the 10th sessions of acupuncture, with a 1-week follow-up after the last session. Participants Groups A and B received five and 10 acupuncture sessions, respectively. Melasma was assessed by using the melanin index (MI), melasma area and severity index (MASI), patient-reported improvement scores, and acupuncture-related adverse events. Results: Out of 113 participants, 67 received five sessions of acupuncture treatment while 39 received 10 sessions. At 1 week after five sessions of acupuncture in Group A, the mean MI decreased by 28.7 (95% CI −38.5 to −18.8, p < 0.001), whereas the median MASI decreased by 3.4 (95% CI −6.9 to −1.2, p < 0.001) points. At 1 week after ten sessions of acupuncture in Group B, the mean MI decreased by 31.3 (95% CI −45 to −17.6, p < 0.001), whereas the median MASI decreased by 5.4 (95%CI −9.9 to −3, p < 0.001) points. The first five sessions of acupuncture had a higher incremental effect than the last five sessions, although there was no statistically significant difference. Twenty-nine participants reported minor side effects. Group B had a risk ratio (RR) of having adverse events 1.8 times (95% CI 1.0–3.4, p = 0.05) compared with Group A. Conclusion: Short acupuncture regimens of 5–10 sessions in melasma seem to be effective and practical with minor side effects.